About Some Phonostylistic Features of Amateur Speech (Texas Journal of Philology, Culture and History, 2023)
In this article, an opinion is expressed about the phonetic phenomena in the speech of amateurs, the stylistic possibilities that emerge as a result of this phenomenon. The article describes the importance of phonostylistic tools in creating meaning, their methodological aspects related to their use in comic texts.